Spontaneous perforation of Meckel’s diverticulum: a rare entity - Zaib, Zainab; Habib, Rohan; Afzal, Muhammad Waqas; Ali, Murad (Journal of the Pakistan Medical Association, 2022)
Meckel's diverticulum is the most common gastrointestinal tract’s congenital abnormality. Spontaneous perforation of Meckel's diverticulum is very rare and can mimic acute appendicitis. Here we report the case of an 11-year-old male patient, who was presented to the Surgical A unit of Ayub Teaching Hospital, Abbottabad on 21st January, 2021 with one-day history of abdominal pain, predominantly in the periumbilical area and right iliac fossa, associated with nausea. On physical examination his abdomen was tense, tender with guarding and generalized rigidity. A provisional diagnosis of perforated appendix or enteric perforation of a hollow viscus was made. The patient had an emergency laparotomy, where a perforated Meckel's diverticulum was discovered. Resection of the portion of gut containing Meckel’s diverticulum was done along with primary anastomosis. Heterotopic gastric mucosa of diverticulitis, associated with perforation was confirmed on histopathology. The patient made an uneventful recovery during postoperative period. ---Continue